Biotreatment of chlorpyrifos in a bench scale bioreactor using Psychrobacter alimentarius T14. Issue 3 (1st February 2016) - Khalid, Saira; Hashmi, Imran
Abstract : Bacteria tolerant to high pesticide concentration could be used for designing an efficient treatment technology. Bacterial strains T14 was isolated from pesticide-contaminated soil in mineral salt medium (MSM) and identified as Psychrobacter alimentarius T14 using 16S rRNA gene sequence analysis. Bench scale bioreactor was evaluated for biotreatment of high Chlorpyrifos (CP) concentration using P. alimentarius T14. Effect of various parameters on bioreactor performance was examined and optimum removal was observed at optical density (OD600 nm): 0.8; pH: 7.2; CP concentration: 300 mg L −1 and hydraulic retention time: 48 h. At optimum conditions, 70.3/79% of CP/chemical oxygen demand (COD) removal was achieved in batch bioreactors. In addition, P. alimentarius T14 achieved 95/91, 62.3/75, 69.8/64% CP/COD removal efficiency with addition of CS (co-substrates), CS1 (yeast extract + synthetic wastewater), CS2 (glucose + synthetic wastewater) and CS3 (yeast extract), respectively. Addition of CS1 to bioreactor could accelerate CP removal rate up to many cycles with considerable efficiency. However, accumulation of 3, 5, 6-trichloro-2-pyridinol affects reactor performance in cyclic mode. First-order rate constant k 1 0.062 h −1 and t 1/2 11.1 h demonstrates fast degradation. Change in concentration of total chlorine and nitrogen could be the result of complete mineralization. Photodegradation of CP in commercial product was more than its pure form. Commercial formulation accelerated photodegradation process; however no effect on biodegradation process was observed. After bio-photodegradation, negligible toxicity for seeds of Triticum aestivum was observed . Study suggests an efficient treatment of wastewater containing CP and its metabolites in batch bioreactors could be achieved using P. alimentarius .